2017
DOI: 10.1103/physrevlett.119.158101
|View full text |Cite
|
Sign up to set email alerts
|

Universality and Specificity in Protein Fluctuation Dynamics

Abstract: We investigate the universal scaling of protein fluctuation dynamics with a site-specific diffusive model of protein motion, which predicts an initial subdiffusive regime in the configurational relaxation. The long-time dynamics of proteins is controlled by an activated regime. We argue that the hierarchical free energy barriers set the time scales of biological processes and establish an upper limit to the size of single protein domains. We find it compelling that the scaling behavior for the protein dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Through multiple investigations considering nine different proteins [83][84][85], the authors have demonstrated that LE4PD is capable of reproducing NMR relaxation time scales as well as nuclear Overhauser effects. The LE4PD model has also recently been employed to identify universal hierarchical scaling features underlying sequence-specific protein dynamics, resembling the directed polymer in random media model [86].…”
Section: G Application To Proteinsmentioning
confidence: 99%
“…Through multiple investigations considering nine different proteins [83][84][85], the authors have demonstrated that LE4PD is capable of reproducing NMR relaxation time scales as well as nuclear Overhauser effects. The LE4PD model has also recently been employed to identify universal hierarchical scaling features underlying sequence-specific protein dynamics, resembling the directed polymer in random media model [86].…”
Section: G Application To Proteinsmentioning
confidence: 99%
“…8,12,13 In this study, we revisit the PCA formalism and formally connect it to a Langevin equation of motion, which was de- veloped to identify slow dynamical modes and study their kinetics in protein dynamics. [14][15][16][17]37 Like the PCA, the LE4PD decomposes the protein's motion into an orthogonal set of collective coordinates or modes.…”
Section: Discussionmentioning
confidence: 99%
“…To account for the effects of energy barriers in the decay of the correlations of the residue fluctuations, such as those shown in Figure 1, the friction coefficient in Eq. 6 is re-normalized using a Kramers-type approach 17,51 : , where F MAD,a = median(| F ( θ a , ϕ a ) − min( F ( θ a , ϕ a )) |) is an average free-energy barrier calculated for LE4PD-XYZ mode a using the median absolute deviation (MAD) 52,53 from the minimum of energy on the surface. This approach rescales the diffusive mode timescales as Using the MAD statistic removes any poorly sampled regions of the energy surface when the calculating the barrier, and using the MAD to rescale the friction coefficients has previously been shown to be effective in describing the slow-down in the decay of the M 1 (t) time correlation function calculated from the LE4PD theory at the 2.5 ns timescale for ubiquitin, 14 the same protein under study here.…”
Section: Contribution Of the High Energy Barriers In The Fluctuation Dynamics Of Proteins Detected By The Pca And Le4pd-xyz Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we make a formal connection between the PCA expressed in the cartesian coordinates of a protein's alpha-carbons and an approach we have developed to analyze the slow modes in protein dynamics, called the Langevin Equation for Protein Dynamics (LE4PD) [13][14][15][16][17][18] . The LE4PD theory, initially formalized as an isotropic equation of motion, is extended here to describe the anisotropic dynamics of proteins in the LE4PD-XYZ method.…”
Section: Introductionmentioning
confidence: 99%